Prevalence of chronic apical periodontitis during the Covid-19 pandemic period at Dental Hospital of Hasanuddin University: intraoral radiographic study: Prevalensi periodontitis apikalis kronis selama periode pandemi Covid-19 di Rumah Sakit Gigi Mulut Universitas Hasanuddin: studi radiografi intraoral - Barunawaty Yunus (Makassar Dental Journal, 2022)
Apical periodontitis is primarily a consequences of root canal infection, be marked with inflammation and tissue destruction pe-riradiculars resulting from interactions between microbial factors and the host immune response. This study is aimed to evalu-ate the prevalence of chronic apical periodontitis (CAP) inpatients of Hasanuddin University Dental and Oral Education Hospital during the Covid-19 pandemic period in 2021. The study was conducted with cross-sectional design. Secondary data in the form of accumulation of the number of patients who came to undergo radiographic examination aged over 12 yearswere then grouped into CAP and non-CAP. Data were analyzed and chi square test was performed to assess the relationship between CAP with gender and age (p<0.05). A total of 222 data were obtained, of which 54% were women. The number of samples who expe-rienced CAP were 33.3% and thelargest age group was 21-30 years (29.7%). There was no significant difference between CAP and gender (p>0.05), but there was a significant difference between CAP and age (p<0.05). CAP depends on the dental condi-tion of patients who are not treated. It was concluded that prevalence of CAP who came for treatment and was detected using intraoral radiography at RSGMP Unhas were 33.3% and most of them were female and in the age group of 21-30 years.